TRANSITION FROM MATERNAL CHRONIC RENAL FAILURE TO PERITONEAL DIALYSIS TREATMENT - Özdemir, Sevda Tűzűn; Tűreyen, Aynur; Yildirim, Yasemin (PROFESSIONAL STUDIES: Theory And Practice, 2024)
Chronic kidney failure (CKF) has become an increasingly important public health issue in our country and worldwide. According to data systems in our country, as of the end of 2022, there were a total of 86,665 patients with chronic kidney failure, and 4.1% of these patients undergo peritoneal dialysis treatment. Peritoneal dialysis requires active participation of the patient in the treatment, and it can lead to negative effects on body image, self-esteem, and sexual relations due to the peritoneal dialysis catheter, causing anxiety and depression in patients and negatively affecting their quality of life. Throughout human life, individuals undergo changes in identity, roles, responsibilities, abilities, and behaviors due to various reasons (illness, pregnancy, death, birth). One of the fundamental duties of nurses is to assist individuals undergoing various transitions in their lives, to support healthy transitions, and to minimize unhealthy transitions. In this study, the process of transition experienced by a healthy woman transitioning to the role of motherhood due to health problems during pregnancy, and transitioning to chronic kidney failure and peritoneal dialysis treatment, is examined based on Meleis' Transition Theory